2021
DOI: 10.31932/jees.v4i2.983
|View full text |Cite
|
Sign up to set email alerts
|

Deixis and Reference Analysis in Jakarta Post: A Content Analysis Research

Abstract: Deixis and reference are parts of pragmatics. These issues are needed to be known by the readers. Deixis and reference were existing in written or spoken language and those materials are learnt by students in university level especially in English education department. These things are essential to be known by the readers or audience. Thus, the aims of the study were to analyse the deixis and reference types in Jakarta Post. The research methodology was a qualitative research with content analysis. The instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Many researchers have analyzed deixis in a lot of kinds of texts, such as, speech, newspapers' articles, song lyrics, novels, teachers' talks, students' talks, and other area of language expressions. Syafryadin et al (2021) investigated the deixis types and reference types in Jakarta Post. They found that all types of dexis were found in Jakarta Post, person, spatial, time, discourse and social: in detail, 300 words of person deixis, 140 Spatial deixis, 90 time deixis, 30 social and 15 discouse deixis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many researchers have analyzed deixis in a lot of kinds of texts, such as, speech, newspapers' articles, song lyrics, novels, teachers' talks, students' talks, and other area of language expressions. Syafryadin et al (2021) investigated the deixis types and reference types in Jakarta Post. They found that all types of dexis were found in Jakarta Post, person, spatial, time, discourse and social: in detail, 300 words of person deixis, 140 Spatial deixis, 90 time deixis, 30 social and 15 discouse deixis.…”
Section: Literature Reviewmentioning
confidence: 99%